Efektivitas Official Development Assistance Jepang terhadap Negara Resipien - Sarah Anabarja (Andalas Journal of International Studies (AJIS))
Japan has been well-known due to its advanced technology innovation particularly in the field of industrial technology. Some Japanese manufactures that based on technological development have become the main supplier of high-technology goods in many countries in the world most importantly in Asia. Since 1970s, Japan government has implemented its foreign assistance called Official Development Assistance (ODA) to developing countries including Indonesia. Japan has assisted the developing countries through its export-credit program. This paper will discuss the effectiveness of ODA and its implementation. In the first part of this paper, it will elaborate the history and structure of Japan’s ODA. In the next part, it will also explain the successful achievement of this program. Besides, it will also examine whether or not the implementation of this assistance has effectively reached its target and goals. The understanding of essential component of development strategy to increase the ODA’s effectiveness is related with the usage of that assistance in the recipient country. This perception is in line with Kevin Morrison (2000) saying the four elements of foreign assistance’s effectiveness particularly the technical assistance of Japan.